Cubosome-based Corticosteroidal Drug Delivery System for Sustained Ocular Delivery: A Pharmacokinetic Investigation - Chakorkar, Snehal Shashikant; Mulla, Jameel Ahmed Sayed Gous (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Fluorometholone is an anti-inflammatory glucocorticoid. It has been used in various ocular inflammatory as well as infectious conditions. Opting for sustained release in ocular drug delivery is a favorable option for managing ocular diseases. To improve efficacy and to overcome side effects, fluorometholone was encapsulated in cubosomal vesicles. Aim In this study, fluorometholone-loaded cubosomal vesicles were prepared using top-down techniques and applying the QbD approach. The optimized formulation releases the drug in a sustained release manner. Materials and Methods The optimization of cubosomal vesicles was conducted using a 32-CDD. The independent parameter was selected: Concentration of both polymers Glyceryl monooleate (GMO) and Poloxamer 407 (P407), sonication time. The desired property for five important critical attributes of fluorometholone-loaded cubosome vesicles, namely % entrapment efficiency, Cumulative drug release, particle size, polydispersity index and Viscosity. Results and Discussion The optimized formulation suggested by the central composite design was the concentration of GMO and P407; sonication times were 0.36 g, 0.46 g and 8 min, respectively. The optimized formulation exhibited % entrapment efficiency, % Cumulative drug release, particle size, polydispersity index and Viscosity were 82.89%, 88.33%, 137.7 μn, 0.22 and 169.3 m.Pas. The results confirm that implementing a QbD approach in cubosomal design leads to demonstrably improved formulation outcomes. The optimized batch was used for further evaluation like pH and Refractive index, Morphological feature evaluation, Release kinetics study, Test for sterility and stability and in vivo pharmacokinetic study. Conclusion The present work confirms the improved ocular bioavailability of fluorometholone-loaded cubosomes.
Keywords: Fluorometholone; Cubosomes; Drug delivery system; Ocular delivery; Quality by Design; Central composite design